ANALISIS RESEPSI PADA VIDEO LIVING WITH MUSLIM WITH TOMMY LIM (Studi pada Masyarakat Non Muslim di Kota Denpasar) - Rinikah, Lia; Alit Suryawati, I Gusti Agung; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2020)
ABSTRACT In addressing the’issue of’intolerance due to*Islamic radical movement activities, Youtube Indonesia and Film Maker Muslim collaborated in the Creators for Change project by releasing Living with Muslim with Tommy Lim in 2018. One of the factors of non-moslem audiences' acceptance is their ability to process the meaning of the messages. This study applied the reception analysis and encoding decoding theory in the process of analyzing the acceptance of messages that occurred to the non-moslem audiences in Denpasar after watching the video, considering the majority of the population is non-moslem. Of the four informants from different backgrounds and religions, the results show that the formed reception was divided into two positions, namely dominant position and negotiated position. Furthermore, the message's acceptability is still in common interaction and does not lead to religious activities.   Keywords: Reception Analysis,Islam, Encoding, and Decoding